Sistematización de experiencias en gestión documental y servicio al cliente en la facultad de ciencias administrativas de la Universidad Técnica De Cotopaxi - García Tapia, Jheniffer Lisset (2019)
The research project is the systematization of experiences that carried out in Administrative Sciences Faculty at Cotopaxi Technical University, the Document Management and Customer Service Topic during the period April 2018-February-2019. The main goal was to analyze the experiences in Documentary Management and Customer Service. Thus, this investigation will contribute and benefit the students and the general public with a good service in the faculty Secretary. In this way, the purpose is to develop the performance activities in effectively and efficiently way. In this perspective, techniques and quality development at the time of: receiving, archiving and preserving all documents types that have been made. Finally, it has been proposed to improve a program that helps improve the enrollment process for students and thus they feel more satisfied with the care provided in the study place. Also, the qualitative approach was considered in it. Surveys were applied as research techniques in order to get and collect all necessary and truthful information into participants’ context on studied systematization object. The data was subjected to a critical analysis of the theoretical framework support. As a consequence, this action has allowed identifying the difficulties in customer service provided by the secretary, especially during the registration period. It has been proposed that a program will be developed to facilitate the enrollment process, which will benefit the faculty. Therefore, students have ease and feel comfortable when purchasing a service during the process.